Proses Disclosure dan Kondisi Psikososial Anak Dengan HIV/AIDS - Deswanti, Arini Dwi; Imelda, Johanna Debora (Jurnal Ilmu Kesejahteraan Sosial, 2016)
HIV-infected children have a longer life expectancy after the invention of antiretroviral treatment. Therefore, a well-prepared HIV status disclosure become a significant issue for children living with HIV/AIDS (CLWHA). Previous studies have shown that disclosing a status of children with chronic illness helps them to cope with the illness. However, delayed disclosure for various reasons which often influenced by parents or caregivers consideration affect children’s psychosocial condition. This paper will illustrate the psychosocial condition of CLWHA in relation to the preparation of their disclosure process.This descriptive study used a qualitative approach with observations, in-depth interviews, and Focus Group Discussion on CLWHA and their parents/caregivers.Not all disclosed CLWHA has a good psychosocial function. The disclosure are affected by the process and the disclosure level. A HIV disclosed child of HIV positive parents has better psychosocial conditions than a child whose disclose are prepared by a pediatrician or than those who partially disclosed by themselves.Disclosing HIV/AIDS status has significantly affected the psychosocial condition of CLWHA. Therefore, it needs to be carefully well planned and well prepared by taking into account the condition of ADHAs and their caregivers to avoid involuntary disclosure.The government needs to formulate policies on disclosure process for CLWHA to maintain the psychosocial condition of the children so that their quality of life can be better increased.